Indo-U.S. Workshop on Challenges of Emerging Infections and Global Health Safety: Summary of a Workshop - National Academy of Sciences (The National Academies Press, 2016)
The United States and India have pledged to deepen the linkages between their people, their businesses, and their governments for the mutual benefit of both countries and for the promotion of global peace, stability, economic growth and prosperity. Both nations are now inclined to improve relations and cooperation, but the nations need specific actions that will yield progress and build confidence and momentum for further cooperation. The Indo-U.S. Workshop on Challenges of Emerging Infections and Global Health Safety, held in November 2014, encouraged scientists from both countries to examine global issues related to emerging and existing infections and global health safety, to share experience and approaches, and to identify opportunities for cooperation to improve practice and research in these areas. This report summarizes the presentations and discussions from the workshop.

Science Literacy: Concepts, Contexts, and Consequences - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
Science is a way of knowing about the world. At once a process, a product, and an institution, science enables people to both engage in the construction of new knowledge as well as use information to achieve desired ends. Access to science2014whether using knowledge or creating it2014necessitates some level of familiarity with the enterprise and practice of science: we refer to this as science literacy. Science literacy is desirable not only for individuals, but also for the health and well- being of communities and society. More than just basic knowledge of science facts, contemporary definitions of science literacy have expanded to include understandings of scientific processes and practices, familiarity with how science and scientists work, a capacity to weigh and evaluate the products of science, and an ability to engage in civic decisions about the value of science. Although science literacy has traditionally been seen as the responsibility of individuals, individuals are nested within communities that are nested within societies2014and, as a result, individual science literacy is limited or enhanced by the circumstances of that nesting. Science Literacy studies the role of science literacy in public support of science. This report synthesizes the available research literature on science literacy, makes recommendations on the need to improve the understanding of science and scientific research in the United States, and considers the relationship between scientific literacy and support for and use of science and research.

Preventing Bullying Through Science, Policy, and Practice - National Academies of Sciences, Engineering,; Medicine
Bullying has long been tolerated as a rite of passage among children and adolescents. There is an implication that individuals who are bullied must have \

Extending Science: NASA's Space Science Mission Extensions and the Senior Review Process - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
NASA operates a large number of space science missions, approximately three-quarters of which are currently in their extended operations phase. They represent not only a majority of operational space science missions, but a substantial national investment and vital national assets. They are tremendously scientifically productive, making many of the major discoveries that are reported in the media and that rewrite textbooks. Extending Science 2013 NASA's Space Science Mission Extensions and the Senior Review Process evaluates the scientific benefits of missions extensions, the current process for extending missions, the current biennial requirement for senior reviews of mission extensions, the balance between starting new missions and extending operating missions, and potential innovative cost-reduction proposals for extended missions, and makes recommendations based on this review.

Making the Living World Engineerable: Science, Practice, and Policy: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
On November 16, 2016, the Forum on Synthetic Biology of the National Academies of Sciences, Engineering, and Medicine's Committee on Science, Technology, and Law hosted a workshop titled Making the Living World Engineerable: Science, Practice, and Policy. The workshop was organized by an ad hoc planning committee to discuss current trends in synthetic biology, including international scientific and technical developments in synthetic biology; possible risks and benefits related to these developments; and legal, regulatory, and policy concerns. This Proceedings of a Workshop-in Brief highlights the presentation of the event.

Achieving Science with CubeSats: Thinking Inside the Box - National Academies of Sciences, Engineering,; Medicine
Space-based observations have transformed our understanding of Earth, its environment, the solar system and the universe at large. During past decades, driven by increasingly advanced science questions, space observatories have become more sophisticated and more complex, with costs often growing to billions of dollars. Although these kinds of ever-more-sophisticated missions will continue into the future, small satellites, ranging in mass between 500 kg to 0.1 kg, are gaining momentum as an additional means to address targeted science questions in a rapid, and possibly more affordable, manner. Within the category of small satellites, CubeSats have emerged as a space-platform defined in terms of (10 cm x 10 cm x 10 cm)- sized cubic units of approximately 1.3 kg each called \

From Research to Reward: Social Science Studies the Most Hazardous Thing on the Road: You - National Academy of Sciences (The National Academies Press, 2016)

Applying an Implementation Science Approach to Genomic Medicine: Workshop Summary - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
Although it is becoming increasingly more common for clinicians to use genomic data in their practices for disease prevention, diagnosis, and treatment, the process of integrating genomic data into the practice of medicine has been a slow and challenging one. Some of the major barriers impeding the incorporation of new genomic technology into clinical practice are: the difficulty of changing routine medical practices to account for the use of genetic testing, the limited knowledge of patients and providers about genomic medicine, assessing sufficient evidence to support the use of genetic tests, privacy and data security issues, and uncertainty about reimbursement. The field of implementation science may be able to provide insights concerning efficient ways to incorporate genomic applications into routine clinical practice. The focus of implementation science studies is to identify integration bottlenecks and optimal approaches for a given setting and ultimately to promote the up-take of research findings. To explore the potential of implementation science to improve the integration of genomics into medicine, the National Academies of Sciences, Engineering, and Medicine held a workshop in Washington, DC, in November 2015. Participants explored the challenges and opportunities of integrating genomic advances into the clinic through the lens of implementation science. This report summarizes the presentations and discussions from the workshop.

Communicating Chemistry: A Framework for Sharing Science: A Practical Evidence-Based Guide - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
A growing body of evidence indicates that, increasingly, the public is engaging with science in a wide range of informal environments, which can be any setting outside of school such as community-based programs, festivals, libraries, or home. Yet undergraduate and graduate schools often don2019t prepare scientists for public communication. This practical guide is intended for any chemist 2013 that is, any professional who works in chemistry-related activities, whether research, manufacturing or policy 2013 who wishes to improve their informal communications with the public. At the heart of this guide is a framework, which was presented in the report Effective Chemistry Communication in Informal Environments and is based on the best available empirical evidence from the research literature on informal learning, science communication, and chemistry education. The framework consists of five elements which can be applied broadly to any science communication event in an informal setting.

Gene Drives on the Horizon: Advancing Science, Navigating Uncertainty, and Aligning Research with Public Values - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
Research on gene drive systems is rapidly advancing. Many proposed applications of gene drive research aim to solve environmental and public health challenges, including the reduction of poverty and the burden of vector-borne diseases, such as malaria and dengue, which disproportionately impact low and middle income countries. However, due to their intrinsic qualities of rapid spread and irreversibility, gene drive systems raise many questions with respect to their safety relative to public and environmental health. Because gene drive systems are designed to alter the environments we share in ways that will be hard to anticipate and impossible to completely roll back, questions about the ethics surrounding use of this research are complex and will require very careful exploration. Gene Drives on the Horizon outlines the state of knowledge relative to the science, ethics, public engagement, and risk assessment as they pertain to research directions of gene drive systems and governance of the research process. This report offers principles for responsible practices of gene drive research and related applications for use by investigators, their institutions, the research funders, and regulators.

From Research to Reward: The Hospital Checklist: How Social Science Insights Improve Health Care Outcomes - National Academy of Sciences (The National Academies Press, 2016)

Obesity in the Early Childhood Years: State of the Science and Implementation of Promising Solutions: Workshop in Brief - Institute of Medicine; National Academies of Sciences, Engineering,; Medicine
On October 6, 2015, the Roundtable on Obesity Solutions of the National Academies of Sciences, Engineering, and Medicine held a workshop titled \

Obesity in the Early Childhood Years: State of the Science and Implementation of Promising Solutions: Workshop Summary - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
Among the many troubling aspects of the rising prevalence of obesity in the United States and elsewhere in recent years, the growth of early childhood overweight and obesity stands out. To explore what is known about effective and innovative interventions to counter obesity in young children, the National Academies of Sciences, Engineering, and Medicine2019s Roundtable on Obesity Solutions held a workshop in October 2015. The workshop brought together many of the leading researchers on obesity in young children to describe the state of the science and potential solutions based on that research. Participants explored sustainable collaborations and new insights into the implementation of interventions and policies, particularly those related to nutrition and physical activity, for the treatment and prevention of obesity in young children. Obesity in the Early Childhood Years summarizes the presentations and discussions from the workshop.

Supporting Family and Community Investments in Young Children Globally: Summary of a Joint Workshop by the National Academies of Sciences, Engineering, and Medicine and the Ethiopian Academy of Sciences - Institute of Medicine; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
To examine the science, policy, and practice surrounding supporting family and community investments in young children globally and children in acute disruptions, the National Academies of Sciences, Engineering, and Medicine held a workshop in partnership with the Ethiopian Academy of Sciences in Addis Ababa, Ethiopia, from July 27-29, 2015. The workshop examined topics related to supporting family and community investments in young children globally. Examples of types of investments included financial and human capital. Participants also discussed how systems can better support children, families, and communities through acute disruptions such as the Ebola outbreak. Over the course of the 3-day workshop, researchers, policy makers, program practitioners, funders, young influencers, and other experts from 19 countries discussed how best to support family and community investments across areas of health, education, nutrition, social protection, and other service domains. This report summarizes the presentations and discussions from the workshop.

Advancing the Discipline of Regulatory Science for Medical Product Development: An Update on Progress and a Forward-Looking Agenda: Workshop Summary - National Academies of Sciences, Engineering,; Medicine
The field of endeavors known as \

Future Directions for NSF Advanced Computing Infrastructure to Support U.S. Science and Engineering in 2017-2020 - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
Advanced computing capabilities are used to tackle a rapidly growing range of challenging science and engineering problems, many of which are compute- and data-intensive as well. Demand for advanced computing has been growing for all types and capabilities of systems, from large numbers of single commodity nodes to jobs requiring thousands of cores; for systems with fast interconnects; for systems with excellent data handling and management; and for an increasingly diverse set of applications that includes data analytics as well as modeling and simulation. Since the advent of its supercomputing centers, the National Science Foundation (NSF) has provided its researchers with state-of-the-art computing systems. The growth of new models of computing, including cloud computing and publically available by privately held data repositories, opens up new possibilities for NSF. In order to better understand the expanding and diverse requirements of the science and engineering community and the importance of a new broader range of advanced computing infrastructure, the NSF requested that the National Research Council carry out a study examining anticipated priorities and associated tradeoffs for advanced computing. Future Directions for NSF Advanced Computing Infrastructure to Support U.S. Science and Engineering in 2017-2020 provides a framework for future decision-making about NSF's advanced computing strategy and programs. It offers recommendations aimed at achieving four broad goals: (1) position the U.S. for continued leadership in science and engineering, (2) ensure that resources meet community needs, (3) aid the scientific community in keeping up with the revolution in computing, and (4) sustain the infrastructure for advanced computing.

An Assessment of the National Institute of Standards and Technology Center for Nanoscale Science and Technology: Fiscal Year 2016 - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
At the request of the National Institute of Standards and Technology (NIST), the National Academies of Sciences, Engineering, and Medicine has, since 1959, annually assembled panels of experts from academia, industry, medicine, and other scientific and engineering communities to assess the quality and effectiveness of the NIST measurements and standards laboratories, of which there are now seven, as well as the adequacy of the laboratories2019 resources. An Assessment of the National Institute of Standards and Technology Center for Nanoscale Science and Technology: Fiscal Year 2016 assesses the scientific and technical work performed by the NIST Center for Nanoscale Science and Technology and the accomplisments, challenges, and opportunities for improvement.

Art, Design and Science, Engineering and Medicine Frontier Collaborations: Ideation, Translation, Realization: Seed Idea Group Summaries (The National Academies Press, 2016)
Science and art were not always two separate entities. Historically, times of great scientific progress occurred during profound movements in art, the two disciplines working together to enrich and expand humanity's understanding of its place in this cosmos. Only recently has a dividing line been drawn, and this seeming dichotomy misses some of the fundamental similarities between the two endeavors. At the National Academies Keck Futures Initiative Conference on Art, Design and Science, Engineering and Medicine Frontier Collaborations: Ideation, Translation, and Realization, participants spent 3 days exploring diverse challenges at the interface of science, engineering, and medicine. They were arranged into Seed Groups that were intentionally diverse, to encourage the generation of new approaches by combining a range of different types of contributions. The teams included creative practitioners from the fields of art, design, communications, science, engineering, and medicine, as well as representatives from private and public funding agencies, universities, businesses, journals, and the science media.

Reaching and Investing in Children at the Margins: Summary of a Joint Workshop by the National Academies of Sciences, Engineering, and Medicine; Open Society Foundations; and the International Step by Step Association (ISSA) - National Academies of Sciences, Engineering,; Medicine
The United Nations Sustainable Development Goals for 2015-2030 strive for a world that is \

Investing in Young Children for Peaceful Societies: Proceedings of a Joint Workshop by the National Academies of Sciences, Engineering, and Medicine; UNICEF; and the King Abdullah Bin Abdulaziz International Centre for Interreligious and Intercultural Dialogue (KAICIID) - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
With the worst human refugee crisis since World War II as the backdrop, from March 16 through March 18, 2016, the National Academies of Sciences, Engineering, and Medicine, in partnership with UNICEF and the King Abdullah Bin Abdulaziz International Center for Inter-religious and Intercultural Dialogue (KAICIID), held a workshop in Amman, Jordan, to explore topics related to investing in young children for peaceful societies. Over the course of the workshop, researchers, policy makers, program practitioners, funders, youth, and other experts came together to understand the effects of conflict and violence on children, women, and youth across areas of health, education, nutrition, social protection, and other domains. The goal of the workshop was to continue to fill in gaps in knowledge and explore opportunities for discourse through a process of highlighting the science and practice. This publication summarizes the presentations and discussions from the workshop.